22.3k views
1 vote
Solve for x.
4x - 8 = -3(2x + 6)

User Anupriya
by
5.0k points

2 Answers

4 votes

Answer:

x=-7

Explanation:

first u wanna multiply (2x+6) which equals 12 the what u wanna do is move the constant to the right which is 4x-8=-36. Then calculate 4x=-36+8. then after that then u should end up with 4x=-28 then u divide it then u end up with ×=-7

User Patrick Beagan
by
4.8k points
5 votes

Answer:

x= -1

Explanation:

First, distribute the -3 through the parentheses

4x-8= -3(2x+6)

= 4x-8= -6x-18

Second, move the variable to the left-hand side and change its sign

4x+6x= -18+8

10x= -10

Divide both sides by 10

x=-1

User Maak
by
4.8k points